A review of the Z(2)-FET 1T-DRAM memory: Operation mechanisms and key parameters - Cristoloveanu, S.; Lee, K. H.; Parihar, M. S.; El Dirani, H.; Lacord, J.; Martinie, S.; Le Royer, C.; Barbe, J. -Ch.; Mescot, X.; Fonteneau, P.; Galy, Ph.; Gamiz, F.; et al. (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
The band-modulation and sharp-switching mechanisms in Z(2)-FET device operated as a capacitorless 1T-DRAM memory are reviewed. The main parameters that govern the memory performance are discussed based on detailed experiments and simulations. This 1T-DRAM memory does not suffer from super-coupling effect and can be integrated in sub-10 nm thick SOI films. It offers low leakage current, high current margin, long retention, low operating voltage especially for programming, and high speed. The Z(2)-FET is suitable for embedded memory applications.
Keywords: CAPACITORLESS 1T-DRAM; BAND-MODULATION; CELL; TECHNOLOGY; DEVICE; NODE; DRAM